Rat macrophage C-type lectin is an activating receptor expressed by phagocytic cells. - Ana Lobato-Pascual (Public Library of Science (PLoS), 2013)
Macrophage C-type lectin (MCL) is a membrane surface receptor encoded by the Antigen Presenting Lectin-like gene Complex (APLEC). We generated a mouse monoclonal antibody for the study of this receptor in the rat. We demonstrate that rat MCL is expressed on blood monocytes and neutrophils, as well as on several tissue macrophage populations, including alveolar and peritoneal cavity macrophages. We also demonstrate MCL expression on a subset of resident spleen macrophages. Immunohistochemistry analysis of the spleen showed staining specifically in the marginal zone and red pulp. Exposure to pro-inflammatory mediators or to yeast cell wall extract (zymosan) increased surface MCL expression on peritoneal macrophages. We characterized a rat myeloid cell line, RMW, which expresses high levels of MCL. We found that MCL co-immunoprecipitated with the activating adaptor protein FcεRIγ in these cells. Moreover, beads coated with anti-MCL antibody increased phagocytosis in the RMW cells. Together, these observations indicate that rat MCL is a receptor that activates phagocytosis in myeloid cells under inflammatory conditions.